Tożsamość miasta w kontekście przemian politycznych, ekonomicznych i społecznych we współczesnej Polsce. Przypadek Kielc - Radziszewska, Joanna Z. (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
City identity can be defined as a historically distinctive attributes that distinguish that city form all the other cities. Identity is influenced by many factors such as: genesis of a city, economic development, spatial arrangements and the picture of a city in the collective mind of its inhabitants. City identity is not permanent feature. It is influenced by political, social and economic changes. The most important factors that influence city identity are: system transformation, globalization, metropolization and European integration. The combination of all these processes and their influences on the identity of contemporary city, such as Kielce, is the aim of this study,